One-year post-vaccination longitudinal follow-up of quantitative sars-cov-2 anti-spike total antibodies in health care professionals and evaluation of correlation with surrogate neutralization test - HASDEMİR GÖKBOĞA, MÜNEVVER UFUK (My University, 2023)
Numerous vaccines have been generated to decrease the morbidity and mortality of COVID-19. This study aims to evaluate the immunogenicity of the heterologous boosts by BioNTech against homologous boosts by CoronaVac at three-month intervals in two health care worker (HCW) cohorts, with or without prior COVID-19, for one year post-vaccination. This is a prospective cohort study in which the humoral responses of 386 HCWs were followed-up longitudinally in six main groups according to their previous COVID-19 exposure and vaccination status. Anti-SARS-CoV-2 spike-RBD total antibody levels were measured and SARS-CoV-2 neutralization antibody (NAbs) responses against the ancestral Wuhan and the Omicron variant were evaluated comparatively using international standard serum for Wuhan and Omicron, as well as with the aid of a conversion tool. The anti-SARS-CoV-2 spike-RBD total Ab and Nab difference between with and without prior COVID-19, three months after two-dose primary vaccination with CoronaVac, was statistically significant (p = 0.001). In the subsequent follow-ups, this difference was not observed between the groups. Those previously infected (PI) and non-previously infected (NPI) groups receiving BioNTech as the third dose had higher anti-SARS-CoV-2 spike total Ab levels (14.2-fold and 17.4-fold, respectively, p = 0.001) and Nab responses (against Wuhan and Omicron) than those receiving CoronaVac. Ab responses after booster vaccination decreased significantly in all groups at the ninth-month follow-up (p < 0.05); however, Abs were still higher in all booster received groups than that in the primary vaccination. Abs were above the protective level at the twelfth-month measurement in the entire of the second BioNTech received group as the fourth dose of vaccination. In the one-year follow-up period, the increased incidence of COVID-19 in the groups vaccinated with two or three doses of CoronaVac compared with the groups vaccinated with BioNTech as a booster suggested that continuing the heterologous CoronaVac/BioNTech vaccination, revised according to current SARS-CoV-2 variants and with at least a six-month interval booster would be an effective and safe strategy for protection against COVID-19, particularly in health care workers.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Sağlık Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Health Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); İmmünoloji; Farmakoloji ve Toksikoloji; BULAŞICI HASTALIKLAR; FARMAKOLOJİ VE ECZACILIK; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Life Sciences (LIFE); IMMUNOLOGY; PHARMACOLOGY & TOXICOLOGY; MOLECULAR BIOLOGY & GENETICS; INFECTIOUS DISEASES; PHARMACOLOGY & PHARMACY; BIOCHEMISTRY & MOLECULAR BIOLOGY; Farmakoloji; İlaç Keşfi; Bulaşıcı hastalıklar; Farmakoloji (tıbbi); Immunology; Pharmacology; Drug Discovery; Infectious Diseases; Pharmacology (medical); COVID-19; heterologous; inactivated; mRNA; vaccine